Mengenal Kebudayaan Suku Bugis - Fatmawati, Fifi; Kurnia, Heri (Jurnal Ilmu Sosial dan Budaya Indonesia, 2023)
Bugis tribal culture is a very complex reality in the lives of Indonesian people. The Bugis tribe, as part of the Deutero Malay group, came to the archipelago after the first wave of migration from mainland Asia, especially Yunan. The name "Bugis" comes from "To Ugi," which refers to the Bugis people. La Sattumpugi, the first king of the Chinese Kingdom in Pammana, Wajo Regency, played a key role in Bugis history. The epic story "La Galigo," the world's greatest literary work, depicts the life journey of Sawerigading, We Cudai's husband, and creates the cultural foundation of the Bugis people. The Bugis community formed several classical kingdoms, such as Luwu, Bone, Wajo, Soppeng, Suppa, Sawitto, Sidenreng, and Rappang. However, the Bugis tribe has a marriage relationship with the Makassar and Mandar tribes. Currently, Bugis people are spread across various districts, creating a transitional area between Bugis and Makassar and Mandar. The Luwu Kingdom is considered to be one of the oldest kingdoms along with Cina, Mario, and Siang. History in the Bone region records seven generations of chaos, which was overcome by the To Manurung figure, known as Manurungnge ri Matajang, who was appointed Arumpone and formed the legislative council "ade pitue."